PERLINDUNGAN HUKUM BAGI PEKERJA MIGRAN INDONESIA TERHADAP LABOUR TRAFFICKING MENURUT HUKUM INTERNASIONAL - Mutiara Nastiti Putri (2023)
Labour trafficking is one of the many types of human trafficking that aims at the exploitation of workers. Indonesia, until now, is still one of the countries in the world to be the source and target of human trafficking crimes, especially in terms of labour trafficking and sexual trafficking. It is known that the targets who are vulnerable to becoming victims of these crimes are migrant workers. Indonesian Migrant Workers as victims of trafficking crimes is a problem that still occurs and is related to the issue of human rights enforcement. This study aims to determine the role of existing legal arrangements and the efforts that can be made by international legal subjects in providing protection for Indonesian Migrant Workers from the crime of labour trafficking. This is a normative legal research conducted using a library research as a data collection method. The sources of legal materials used are primary and secondary legal materials. The results of the research show that the existing arrangements or regulations are not sufficient to provide protection for Indonesian Migrant Workers from the crime of labour trafficking. This can be seen from the number of cases, the lack of emphasis on cooperation agreements and Indonesia's performance in dealing with trafficking cases. To optimize protection efforts, Indonesia as a country can monitor the implementation and harmonize ceritain goals in cooperation with other countries through international agreements and ratify essential international conventions. The International Labor Organization (ILO) and ASEAN as international organizations also help provide protection for Indonesian Migrant Workers through their role as instruments.